Transplanted human cord blood-derived unrestricted somatic stem cells improve left-ventricular function and prevent left-ventricular dilation and scar formation after acute myocardial infarction. Issue 1 (2nd June 2008) - Ghodsizad, A; Niehaus, M; Kögler, G; Martin, U; Wernet, P; Bara, C; Khaladj, N; Loos, A; Makoui, M; Thiele, J; Mengel, M; Karck, M; et al.
Abstract : Objective: Functional improvement after acute myocardial ischaemia (MI) has been achieved by transplantation of different adult stem and progenitor cell types. It is controversial whether these cell types are able to form novel functional myocardium. Alternatively, graft-related or immune-related paracrine mechanisms may preserve existing myocardium, improve neovascularisation, affect tissue remodelling or induce endogenous de novo formation of functional myocardium. We have applied an alternative somatic cell type, human cord-blood-derived unrestricted somatic stem cells (USSCs) in a porcine model of acute MI. Methods: USSCs were transplanted into the acutely ischaemic lateral wall of the left ventricle (LV). LV dimension and function were assessed by transoesophageal echocardiography (TEE) pre-MI, immediately post-MI, 48 hours and 8 weeks after USSC injection. Additionally, apoptosis, mitosis and recruitment of macrophages were examined 48 hours post-engraftment. Results: Gender-specific and species-specific FISH/immunostaining failed to detect engrafted donor cells 8 weeks post-MI. Nevertheless, cell treatment effectively preserved natural myocardial architecture. Global left ventricular ejection fraction (LVEF) before MI was 60% (7%). Post-MI, LVEF decreased to 34% (8%). After 8 weeks, LVEF had further decreased to 27% (6%) in the control group and recovered to 52% (2%) in the USSC group (p<0.01). Left-ventricular end-diastolic volume (LVEDV) before MI was 28 (2) ml. 8 weeks post-MI, LVEDV had increased to 77 (4) ml in the control group. No LV dilation was detected in the USSC group (LVEDV: 26 (2) ml, p<0.01). Neither apoptosis nor recruitment of macrophages and mitosis were different in either groups. Conclusions: Transplantation of USSCs significantly improved LV function and prevented scar formation as well as LV dilation. Since differentiation, apoptosis and macrophage mobilisation at infarct site were excluded as underlying mechanisms, paracrine effects are most likely to account for the observed effects of USSC treatment.